The Use of The Braille Qur’an As A Medium of Processing For The Disabled Community (Study Of The Blind Group) - Mutrofin, Mutrofin; Osman, Rasha Osman Abdel Haliem; Putri, Siti Shofiatur Rohmawati Din; Mukarromah, Atikalailatul (IAIN Ponorogo, 2024)
The blind group are persons with physical disabilities who have visual impairments. The blind are classified into two types, namely unable to see totally (totally blind) or blind, and able to see with very minimal intensity (low vision). Blind people often have difficulty receiving da'wah messages, because they only rely on hearing to catch the message. So that the right da'wah media is needed to make it easier for the blind in learning Islamic teachings. Preaching to the blind also requires specific strategies and methods of preaching, namely the method of preaching bil-hal delivered by mau'idzah al-hasanah. Through this research, the writer wants to know the level of effectiveness of the Braille Al-Qur'an as a media for preaching the disabled community, especially the blind group. This study uses qualitative methods with literature review data collection techniques. According to the results of the study, the use of the Braille Qur'an is quite effective in introducing Allah's words to the blind because they are textual (can be touched/touched) and sound. With all its advantages, there are several inhibiting factors for the Braille Qur'an as a da'wah medium for the blind.